Proces zmian w organizacji i technologii produkcji wielkopiecowej nad rzeką Bobrzą w Staropolskim Okręgu Przemysłowym w XVI-XVIII wieku - Czmuchowski, Adam (The process of changes in the organisation and technology of large-furnace production by Bobrza river into old Polish industrial district in the 16th-18th century, 2007)
The article describes goods of Cracov bishops which are currently situated in the area of Kielce city. At that time, the industrial district contained many of cities at various level of the industrial development. The article presents the industrial district from the side of changes and technological innovations used during the iron melting. It also includes how technological innovations, derived from West Europe, had been used in those times. This fact contradicts the of the industrial backwardness of the Republic in the 16th-18,h century.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 45-69